A phase 3 study of ravulizumab to protect patients with chronic kidney disease from cardiac surgery-associated acute kidney injury and major adverse kidney events (ARTEMIS) - Marlies Ostermann; David C. Corteville; Kent Doi; Jay L. Koyner; Andre Lamy; Gerry Li; Christine M. Solinsky; Pamela D. Winterberg; William T. Smith; Ravindra L. Mehta; Patrick T. Murray; Andrew D. Shaw; et al. (Trials)
Abstract Background Cardiac procedures, particularly those requiring cardiopulmonary bypass (CPB), are associated with the development of cardiac surgery-associated acute kidney injury (CSA-AKI). Development of CSA-AKI occurs as a result of inflammation, uncontrolled complement activation, and kidney cell damage. In patients with preoperative renal impairment, such as those with chronic kidney disease (CKD), there is an increased risk of both CSA-AKI and poorer clinical outcomes. Currently, there are limited effective, targeted pharmacological interventions for the prevention or treatment of CSA-AKI, although emerging therapies are being investigated, particularly in patients with existing CKD. The ARTEMIS (RAvulizumab to PRotect PaTients with Chronic Kidney DisEase froM CSA-AKI and Subsequent Major Adverse Kidney Events) trial will assess the efficacy and safety of ravulizumab (a complement C5 inhibitor) in reducing the risk of major adverse kidney events (MAKE) in patients with preoperative CKD undergoing non-emergent cardiac surgery with CPB. Methods This trial is currently recruiting patients with CKD who have planned cardiac surgery requiring CPB including coronary artery bypass grafting, valve replacement or repair, or combined procedures. This is a phase 3, randomized, double-blind, placebo-controlled, global study assessing the efficacy and safety of a single preoperative dose of ravulizumab. These outcomes will be assessed using the occurrence of MAKE and its components, as well as the occurrence and severity of CSA-AKI throughout the study period. Discussion Complement activation is known to occur during and after cardiac procedures as a result of CPB and ischemia–reperfusion injury, leading to a cycle of cell damage and death. Therefore, it is hypothesized that preoperative administration of ravulizumab will provide immediate and complete complement inhibition, which will be sustained throughout the surgical period, preventing the uncontrolled complement activation associated with the development of CSA-AKI, thus minimizing poor outcomes for patients. Trial registration ClinicalTrials.gov NCT05746559. Registered on February 27, 2023.